Prevalence of human herpesvirus 8 antibodies in the population of Belém, Pará, Brazil - Ronaldo B. FREITAS; Maria Rute FREITAS; Alexandre C. LINHARES (Universidade de São Paulo (USP), 2002)
Serum samples from 497 children and adults inhabiting two neighbourhoods (Guamá and Terra Firme) in Belém, Pará, North Brazil were screened for the presence of human herpesvirus 8 (HHV-8) antibody using an enzyme-linked immunosorbent assay. An overall 16.3% prevalence was found for these urban communities. Taken both genders together, prevalence rates of HHV-8 antibody increase gradually, across age-groups, ranging from 12.0% to 33.3%. When seroprevalence is analysed by gender, similar rates are found for female (18.4%) and male (14.0%) individuals. In the former gender group, seroprevalence rates increased from 10.3%, in children £ 10 years of age, to 30.0% in adults 41-50 years of age. Conversely, among male subjects, the prevalence of HHV-8 antibodies decreased from 13.3% in children/young adults aged £ 10 to 20 years of age to 6.1% in adults aged 21-30 years. From the 31-40 year-old group male onwards, seropositivity rates increased gradually, ranging from 8.3% to 66.7%. A significant difference in seropositivity rates was noted when comparing 21-30 age groups for female and male subjects: 23.3% and 6.1%, respectively (P = 0.03). Geometric mean optical densities were found to increase slightly from the lower to the higher age-groups. Our data suggest that transmission of HHV-8 occurs frequently in the general urban population of Belém, and that prevalence of antibody seems to increase with age.